The Effect of Using Animation Video Towards Students’ Vocabulary Mastery at The Ninth Grade Student of MTs MII Jiput Pandeglang in Academic Year 2021/ 2022 - Anah, Anah; Novari, Ari Fajria; Gumelar, Rizdki Elang (Universitas Mathla'ul Anwar Banten, 2022)
This research aims to investigate the implementation of animation video in improving students’ vocabulary mastery at ninth grade students of MTs MII Jiput. The research used quantitative approach, while the method used quasi experimental method with pre-test and post-test design. The data collecting technique used pre-test, treatment and post-test. The data was obtained from 2 classes, namely experimental and control class. The experimental class for this research was IX A, while the control class was IX B. Each class consists of 28 students. The total number of the sample was 56 students. The experimental class’s mean score on the pre-test was 54.64, while the control class’s mean score on the pre-test was 50.78. Furthermore, the post-test result showed that the mean score of experimental class was 71.82, while the mean score of control class was 58.60. The hypothesis calculation was done by using SPSS 22. The result of hypothesis showed that r-count is smaller than r-table (0.00 < 0.05) it means that there is significant effect of using Animation video to students’ vocabulary mastery at the Ninth grade of MTs MII Jiput.